East Antarctic sources of extensive Lower–Middle Ordovician turbidites in the Lachlan Orogen, southern Tasmanides, eastern Australia - Glen, R.; Fitzsimons, Ian; Griffin, W.; Saeed, A. (Taylor & Francis Co Ltd, 2017)
Lower to upper Middle Ordovician quartz-rich turbidites form the bedrock of the Lachlan Orogen in the southern Tasmanides of eastern Australia and occupy a present-day deformed volume of ~2–3 million km3. We have used U–Pb and Hf-isotope analyses of detrital zircons in biostratigraphically constrained turbiditic sandstones from three separate terranes of the Lachlan Orogen to investigate possible source regions and to compare similarities and differences in zircon populations. Comparison with shallow-water Lower Ordovician sandstones deposited on the subsiding margin of the Gondwana craton suggests different source regions, with Grenvillian zircons in shelf sandstones derived from the Musgrave Province in central Australia, and Panafrican sources in shelf sandstones possibly locally derived. All Ordovician turbiditic sandstone samples in the Lachlan Orogen are dominated by ca 490–620 Ma (late Panafrican) and ca 950–1120 Ma (late Grenvillian) zircons that are sourced mainly from East Antarctica. Subtle differences between samples point to different sources. In particular, the age consistency of late Panafrican zircon data from the most inboard of our terranes (Castlemaine Group, Bendigo Terrane) suggests they may have emanated directly from late Grenvillian East Antarctic belts, such as in Dronning Maud Land and subglacial extensions that were reworked in the late Panafrican. Changes in zircon data in the more outboard Hermidale and Albury-Bega terranes are more consistent with derivation from the youngest of four sedimentary sequences of the Ross Orogen of Antarctica (Cambrian–Ordovician upper Byrd Group, Liv Group and correlatives referred to here as sequence 4) and/or from the same mixture of sources that supplied that sequence. These sources include uncommon ca 650 Ma rift volcanics, late Panafrican Ross arc volcanics, now largely eroded, and some <545 Ma Granite Harbour Intrusives, representing the roots of the Ross Orogen continental-margin arc. Unlike farther north, Granite Harbour Intrusives between the Queen Maud and Pensacola mountains of the southern Ross Orogen contain late Grenvillian zircon xenocrysts (derived from underlying relatively juvenile basement), as well as late Panafrican magmatic zircons, and are thus able to supply sequence 4 and the Lachlan Ordovician turbidites with both these populations. Other zircons and detrital muscovites in the Lachlan Ordovician turbidites were derived from relatively juvenile inland Antarctic sources external to the orogen (e.g. Dronning Maud Land, Sør Rondane and a possible extension of the Pinjarra Orogen) either directly or recycled through older sedimentary sequences 2 (Beardmore and Skelton groups) and 3 (e.g. Hannah Ridge Formation) in the Ross Orogen. Shallow-water, forearc basin sequence 4 sediments (or their sources) fed turbidity currents into outboard, deeper-water parts of the forearc basin and led to deposition of the Ordovician turbidites ~2500–3400 km to the north in backarc-basin settings of the Lachlan Orogen.